THE INFLUENCE OF LEADERSHIP, COMPENSATION, AND WORK ENVIRONMENT ON JOB SATISFACTION OF EMPLOYEES OF PT BIRO STATISTIK INDONESIA BATAM WITH WORK PRESSURE AS INTERVENING VARIABLE - Rusdin Haluddin; Bambang Satriawan; Muammar Gaddafi (SEAN Institute, 2022)
The purpose of this research is to only examine several factors that affect the level of job satisfaction of BKI employees, namely leadership, compensation, work environment, and work pressure. The population in this study were employees of PT BKI Batam. The method used for sampling is the census method. The sample used in this study is the same as the total population of the study, namely 130 people. This research data was analyzed quantitatively using SEM PLS with Smart PLS version 3.0 tool. The test results using confirmatory factor analysis showed that the research data used were valid and reliable and normally distributed. The results of hypothesis testing indicate that leadership has a significant effect on work pressure; Compensation has a significant effect on work pressure; Work environment has no significant effect on work pressure; Work pressure has a significant effect on job satisfaction; Leadership has a significant effect on job satisfaction; Compensation has no significant effect on job satisfaction; Work environment has no significant effect on job satisfaction; Leadership has a significant effect on job satisfaction through work pressure as an intervening variable; Compensation has a significant effect on job satisfaction through work pressure as an intervening variable; Work environment has no significant effect on job satisfaction through work pressure as an intervening variable. The test results show that the SRMR value is 0.081, which is smaller than 0.100, it can be concluded that the research model is a fit.